Game-Based Learning Courseware for Pre-School Children for Healthy Eating - Almomani, Malek Ahmad Theeb (2012)
Game Based Learning (GBL) is still one of the most effective teaching strategies to enhance learning. Overweight and obesity are considered as dangerous problem around the world. Moreover, they have a direct relation with many health problems and diseases. This project helps to improve information through a project about overweight and obesity among pre-school children in UUM kindergarten. The project will propose a courseware Happy Healthy Meal (HHM) prototype for healthy eating. Each child can interact with a game to realize which are health and unhealthy food. This project focuses on pre-school in UUM kindergarten. The study will adopt the Vaishnavi & Kuechler methodology and ADDIE model to develop the prototype.